Bone Marrow Cytomorphology And Clinico-Hematological Profile of Metastatic Solid Tumors: A 5-Year Audit from A Tertiary Care Centre in Northern India - Kumar, Vijay; Sardana, Rohan; Kishore, Manjari; Marwah, Sadhna; Nigam, A S; Bhardwaj, Minakshi (Annals of Pathology and Laboratory Medicine, 2019)
Introduction: Metastasis to bone marrow by solid malignancies is a rare event and it upgrades the tumor thereby worsening the prognosis. This is caused by an impaired response to therapy and other manifestation resulting from decreased hematopoiesis. The common malignancies to metastasize in male and female are carcinoma prostate and carcinoma breast, respectively. It is noted that metastasis from small round cell tumor (SRCT) predominates in children. Here, we present a series of cases of bone marrow metastasis by solid organ malignancies over a period of 5 years. Objectives: The aim of this study was to investigate the clinical and hematological characteristics of patients with BM metastases of solid tumors diagnosed by bone marrow (BM) aspiration. Materials & methods: In this study, we reviewed 3520 bone marrow aspirates in our hospital from January 2013 to December 2017. Patients diagnosed with solid malignancies metastasizing to bone marrow were selected. Results: We found a total of 26 cases of solid malignancies with metastasis to bone marrow. The age of the patients ranged from 2–88 years (mean age of 46 years). Most of the patients were adults (19/26), of which 77.7% were males. Seven of the 26 patients were in the pediatric age group, with an age range of 2-11 years. Various malignancies metastasizing to marrow were evaluated and clinical and hematological correlation was done. The common presenting sign & symptoms were fever, anorexia and bodyache and organomegaly. Anemia was the most common hematological finding at the time of admission. Carcinoma prostate was the most common metastatic tumor in adults and small round cell tumor in children. Conclusion: BM is one of the important and infrequent sites of metastasis of solid tumors. Detection of bone marrow metastasis has significant clinical implication with impact on therapeutic decisions and is associated with poor prognosis. Aspiration of the BM provides an easy and quick way of detecting involvement, however, biopsy with immunohistochemical and/or molecular techniques may be needed in case of microscopical tumor burden.